A plant health management system for aphididae on lettuce under variable shadehouse conditions in the central Free State, South Africa - Pretorius, Rudolph Johannes (Bloemfontein : Central University of Technology, Free State, 2008)
Aphids (Hemiptera: Aphididae) are amongst the most destructive insects in agricultural crop production systems. This reputation stems from their complex life cycles which are mostly linked to a parthenogenetic mode of reproduction, allowing them to reach immense population sizes within a short period of time. They are also notorious as important and efficient vectors of several plant viral diseases. Their short fecund life cycles allow them to be pests on crops with a short growth period, e.g. lettuce (Lactuca sativa L.). It is common practice to provide this crop with some degree of protection from environmental extremes on the South African Highveld. Shadehouses are popular in this regard, but aphids are small enough to find their way into these structures, and their presence on lettuce is discouraged due to phytosanitary issues. In addition, the excessive use of insecticides is criticized due to the negative influence on human health, and because aphids can rapidly develop resistance. This necessitates the use of alternative control options in order to suppress aphid numbers. Biological control is popular in this regard and the use of predatory ladybirds (Coleoptera: Coccinellidae) is a popular choice. This study investigated the aphid and coccinellid species complex encountered under varying shadehouse conditions on cultivated head lettuce in the central Free State Province (South Africa). Their seasonality was also examined, along with variations in their population size throughout a one-year period. Finally, the impact of varying aphid populations on some physical characteristics of head lettuce was examined, and recommendations for aphid control (using naturally occurring coccinellid predators) were made. Two shadehouse structures were evaluated during this study. One was fully covered with shade netting and designed to exclude the pugnacious ant, Anoplolepis custodiens (Hymenoptera: Formicidae), while the other was partially covered with shade netting (on the roof area) allowing access to the ants. Six cycles of head lettuce were planted and sampled four times during each cycle. These were scheduled to monitor the seedling, vegetative and heading stage of lettuce. Four important aphid species were recorded on the lettuce, namely Acyrthosiphon lactucae, Nasonovia ribisnigri, Myzus persicae and Macrosiphum euphorbiae. Both structures harboured similar aphid and coccinellid species, but their population dynamics differed. A. lactucae dominated in the absence of A. custodiens in the fully covered structure (whole study), while N. ribisnigri dominated in the partially covered structure in the presence of these ants during the warmer months (December – January). M. euphorbiae replaced this species as the dominant species in the absence of A. custodiens (April – September). M. persicae occured during the winter (May – August) in the fully covered structure. Promising coccinellid predators were Hippodamia variegata and Scymnus sp. 1, and to a lesser extent, Exochomus flavipes and Cheilomenes lunata. However, the fully covered structure hampered the entrance of the larger adult coccinellid species, resulting in their lower occurrence. Aphid and coccinellid activity peaked during the summer months (October – January), and the fully covered structure attained the highest aphid infestation levels and coccinellid larval numbers during this time. On the other hand, aphid numbers were higher in the partially covered structure during the cooler months of the year (April – July) and this structure also harboured more adult coccinellids. In most cases, aphid infestation levels did not affect the amount of leaves formed. However, symptomatic damage in terms of head weight reduction did occur under severe infestation levels. Specific environmental conditions within a shadehouse structure concurrently contributed to this reduction, with less favourable conditions accelerating this condition. Results from this study have shown that even though the type of shadehouse structure does not influence the insect species complex found on lettuce, it does have an influence on detrimental and beneficial insect population dynamics. Aphid species infesting lettuce have been identified, along with coccinellid predators that could potentially be used in their control. Both types of structures had advantages and disadvantages, and therefore, decisions concerning shadehouses should not be focused on which type of structure to use, but rather which type of structure to use during different seasons of the year.
Thesis (M. Tech) --Central University of Technology, Free State, 2008
Keywords: Central University of Technology, Free State - Dissertations; Lettuce - Diseases and pests; Phytopathogenic microorganisms - Control; Aphids; Diseases - Seasonal variations; Gardening in the shade; Mite-eating ladybirds; Insects as biological pest control agents; Dissertations, academic - South Africa - Bloemfontein